Total hip arthroplasty for femoral neck fracture with pyoderma gangrenosum patient: A case report - She, Guo Rong (Int J Surg Case Rep, 2016)
INTRODUCTION: Pyoderma gangrenosum is a rare inflammatory aseptic, ulcerative neutrophilic dermatosis which manifest as skin recurrent, painful ulcers. PRESENTATION OF CASE: A 65-year-old man with pyoderma gangrenosum underwent left total hip arthroplasty because of femoral neck fractures. Glucocorticoid, antibiotic, anticoagulant drug, etc. were given in perioperative period. Complication of pyoderma gangrenosum was prevented successfully in perioperative period. DISCUSSION: No consensus has been reached about whether to use glucocorticoid, as well as the dosage and administration, in perioperative periods for pyoderma gangrenosum patients as prophylactic means of wound complication. CONCLUSION: We herein report a case of pyoderma gangrenosum patient underwent total hip arthroplasty, meanwhile raise the issue of management in perioperative period for pyoderma gangrenosum patient, especially explore series of standardized therapies for this disease during arthroplasty.